Renewable Energy and Energy Efficiency: Assessment of Projects and Policies - Thayer, Mark (Asian Journal of Applied Economics, 2016)
This book provides the analytical tools, based on financial and non-financial criteria, to systematically evaluate the important renewable and efficient energy technologies. It is written as a practical textbook at the M.Sc level or final year B.Sc level to train economists and other analysts in both individual project appraisal and the larger scale assessment of energy policy. This book could be used as stepping stone for students whose ultimate objective is the pursuit of a Ph.D.